Explaining the framework of sustainable competitiveness in the direction of spatial development of Arak District - Mina Eftekharnia; Keramatollah Ziari; Majid Naderi (تحقیقات کاربردی علوم جغرافیایی)
Today, the concept of competition has spread in the world in such a way that all countries and governments at the national, regional or local levels are looking for a way to expand and improve economic conditions in favor of investments to stimulate competitiveness. The study of regional development strategies is defined through more competitiveness in the field of capitalist relations and there is less indication of sustainable development concept. On the other hand, due to the complex relationship between environmental, social and economic systems, with the introduction of the concept of competitiveness in the development process, regardless of other subsystems, the field of environmental and social damage in urban and regional systems has arisen and consequences Such as uneven development, increasing social disparities and inequalities and environmental pollution, increasing energy consumption, traffic and other social, cultural and environmental issues; In a way that many metropolises of the world and even Iran are involved with these issues now. In this research, due to the nature of the research, library methods have been used to review the theoretical literature related to the research and to identify indicators related to spatial analysis, content analysis methods have been used. In this regard, first, the activities with competitive advantage in Arak District have been analyzed, spatially using the indexing method and the position of cities has been determined based on the ability to compete in activities with competitive advantage. Then, according to the outlined landscape for Arak District, strategies, policies and spatial rules for use in the region have been written.